Three Halloween genes from the Varroa mite, Varroa destructor (Anderson & Trueman) and their expression during reproduction. Issue 3 (8th December 2014) - Cabrera, A. R.; Shirk, P. D.; Evans, J. D.; Hung, K.; Sims, J.; Alborn, H.; Teal, P. E. A.
Abstract The ecdysteroid biosynthetic pathway involves sequential enzymatic hydroxylations by a group of enzymes collectively known as Halloween gene proteins. Complete sequences for three Halloween genes, spook (Vdspo), disembodied (Vddib) and shade (Vdshd), were identified in varroa mites and sequenced. Phylogenetic analyses of predicted amino acid sequences for Halloween orthologues showed that the acarine orthologues were distantly associated with insect and crustacean clades indicating that acarine genes had more ancestral characters. The lack of orthologues or pseudogenes for remaining genes suggests these pathway elements had not evolved in ancestral arthropods. Vdspo transcript levels were highest in gut tissues, while Vddib transcript levels were highest in ovary‐lyrate organs. In contrast, Vdshd transcript levels were lower overall but present in both gut and ovary‐lyrate organs. All three transcripts were present in eggs removed from gravid female mites. A brood cell invasion assay was developed for acquiring synchronously staged mites. Mites within 4 h of entering a brood cell had transcript levels of all three that were not significantly different from mites on adult bees. These analyses suggest that varroa mites may be capable of modifying 7‐dehydro‐cholesterol precursor and hydroxylations of other steroid precursors, but whether the mites directly produce ecdysteroid precursors and products remains undetermined.